WIfI Classification Based Analysis of Risk Factors for Outcomes in Patients with Chronic Limb Threatening Ischaemia after Endovascular Revascularisation Therapy. (April 2023) - Chen, Zheng; Tan, Tze-Woei; Zhao, Yu; Jiang, Chuli; Zeng, Qiu; Fan, Gaoxiang; Zhang, Wei; Li, Fenghe
Abstract : Objective: The evaluation of limb status with the Wound, Ischaemia, and foot Infection (WIfI) classification and the assessment of patient risks combined with systemic factors, are recommended in patients with chronic limb threatening ischaemia (CLTI). However, there is little evidence of the application of the WIfI classification in the Chinese population. This study aimed to verify the use of the WIfI classification in a Chinese patient population, and to further identify local and systemic independent predictors of adverse CLTI outcomes. Methods: A total of 474 patients who underwent endovascular therapy (EVT) for CLTI in a tertiary hospital between July 2017 and September 2020 were included in this retrospective study. The outcomes included one year major adverse limb events (MALEs), one year all cause mortality, and one year amputation free survival (AFS). Cox regression was used to analyse the association between risk factors and adverse outcomes. Results: In total, 104 (21.9%) all cause deaths were recorded. The rate of MALEs was 17.5%, while the AFS was 71.9%. Multivariable analysis revealed that a body mass index (BMI) < 18.5 kg/m 2 ( p = .002), a left ventricular ejection fraction (LVEF) < 50% ( p < .001), and WIfI wound grade ( p < .001) were independent risk factors for MALEs, while age ≥ 77 years ( p = .031), BMI < 18.5 kg/m 2 ( p < .001), coronary heart disease ( p = .040), and WIfI clinical stages ( p = .021) were independent risk factors for death in patients with CLTI. Age ≥ 77 years ( p = .003), BMI < 18.5 kg/m 2 ( p < .001), coronary heart disease ( p = .012), LVEF < 50% ( p < .001), WIfI wound grade ( p = .004), and WIfI clinical stages ( p = .044) were independently associated with a decreased AFS rate. Conclusions: This study has confirmed the predictive ability of the WIfI classification for Chinese patients with CLTI who underwent EVT. Wound grade was the most sensitive and important risk factor of the three components of WIfI. In addition, systemic factors should be considered to ensure a more accurate prognosis prediction and appropriate clinical decision making in patients with CLTI.